Hypotheses of the quality of operation of the satellite radio navigation system with multi-tone observation and non-Gaussian errors - Харченко, В. П.; Кукуш, О. Г.; Бабак, Є. А. (Proceedings of National Aviation University (archive), 2021)
The mathematical model of calculation of the set of pseudo-distances eid of the control-correcting station to the navigation constellation and detection and removal from the process of determining the coordinates of the consumer of satellites that transmit improbable information is considered.